Development of the program for selftuning a proportalintegraldifferential controller with an additional controlling action - Dovhopolyi, Yaroslav; Manko, Gennady; Trishkin, Vladislav; Shvachka, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
The development of tuning tools proceeds in the direction of broadening the range of supported controllers, using artificial intelligence techniques, methods of diagnosis, development of the user interface. One of the constituent factors of the complex problem on control tasks is the automated maintenance of parameters at the assigned level using proportional-integral-differential (PID) controllers. The spread of the algorithm is limited by the complexity of tuning (non-linearity of the object, external disturbances) to ensure the desired quality. We proposed the structures of PID-controllers with an additional controlling action of the differentiator (PID-CACD). The structure of the controllers includes additional differentiation unit whose input receives the output signal proportional to the sum of output signals of one (two, three) components of a standard PID-controller. The output signal of the additional unit is added to the output signal of the PID-controller as an additional controlling action. The settings of PID-CACD are calculated using the express-method. Dependences of settings on the dynamic characteristics of the object are obtained based on the experimental-statistical data while conducting the classic single-factor experiment and changing one of the dynamic characteristics. The control quality is determined based on the indicators: over-regulation, time of control. It is established that the proposed controller ensures the desired form of ACS transitional characteristic for indicators: over-regulation, time of control. The possibility of creating a graphical user interface of auto-tuning in the MatLab programming environment is shown. The proposed software automates all stages of development: identification of the object, calculation of controller's settings, construction of the transitional characteristic, controller's quality assessment; manual fine-tuning based on the user's experience is also featured